A Critical Analysis of the Financial Efficiency of the Steel Industry in India. (September 2016) - Paul, Pinku; Mukherjee, Paroma Mitra
When one analyses a company's potential for investment, one has to examine its financial performance from a different angle. A company may be a profitable one but could it do more given the assets it has at its disposal? Management efficiency ratios compare what a company owns to its sales or profit performance and inform investors about a company's ability. It helps to use what it has to generate the most profit possible for owners and shareholders. In this study, management efficiency is calculated for five major players of steel industry. To calculate the efficiency, five important ratios—inventory turnover, debtor turnover, investment turnover, fixed assets turnover and total assets turnover ratios are taken into consideration. The study is conducted from 2006 to 2015. Mean and two-way ANOVA is used to test the hypothesis.